QScratch: introduction to quantum mechanics concepts through block-based programming - Escanez-Exposito, Daniel; Rodriguez-Vega, Marcos; Rosa-Remedios, Carlos; Caballero-Gil, Pino (EPJ quantum technology, 2025)
This article introduces QScratch, a novel educational tool designed to introduce fundamental quantum concepts and principles. It is an extension of the high-level block-based visual programming language Scratch, developed by the MIT Media Lab. The quantum concepts taught are presented in a simple and illustrative, yet rigorous way. The selection of topics and their adaptation for this project has been made taking into account the huge complexity of the subject, developing specific intuitive blocks to model the quantum behaviours of superposition, entanglement and measurement. A pilot study carried out with a group of 68 students has demonstrated the validity of the software developed as a tool for introducing complex quantum physics concepts. Thus, the proposed tool complements the original Scratch tool, advancing in the construction of Science, Technology, Engineering and Mathematics (STEM) tools that facilitate the introduction of quantum concepts to everyone.